Найти f‘(x0), f(x)=4x+1/x+3, x0=-2

Найти f‘(x0), f(x)=4x+1/x+3, x0=-2
Гость
Ответ(ы) на вопрос:
Гость
[latex] (\frac{4x+1}{x+3})'= \frac{(4x+1)'(x+3)-(4x+1)(x+3)'}{(x+3)^2}= \frac{4(x+3)-(4x+1)}{x^2+6x+9}= \frac{4x+12-4x-1}{x^2+6x+9}= \\ \frac{11}{x^2+6x+9} \\ \\ x_0=-2 \\ \\ \frac{11}{(-2)^2+6(-2)+9}= \frac{11}{4-12+9}=11 [/latex]
Гость
f`(x)=[(4x+1)`(x+3)-(4x+1)(x+3)`]/(x+3)²=[4*(x+3)-1*(4x+1)]/(x+3)²=(4x+12-4x-1)/(x+3)²= =11/(x+3)² f`(-2)=11/(-2+3)²=11/1=11
Не нашли ответ?
Ответить на вопрос
Похожие вопросы